Effective analgesic doses of tramadol or tapentadol induce brain, lung and heart toxicity in Wistar rats. (15th June 2017) - Faria, Juliana; Barbosa, Joana; Leal, Sandra; Afonso, Luís Pedro; Lobo, João; Moreira, Roxana; Queirós, Odília; Carvalho, Félix; Dinis-Oliveira, Ricardo Jorge
Abstract: Tramadol and tapentadol are extensively prescribed for the treatment of moderate to severe pain. Although these drugs are very effective in pain treatment, the number of intoxications and deaths due to both opioids is increasing, and the underlying toxic mechanisms are not fully understood. The present work aimed to study the potential biochemical and histopathological alterations induced by acute effective (analgesic) doses of tramadol and tapentadol, in Wistar rats. Forty-two male Wistar rats were divided into different groups: a control, administered with normal saline solution, and tramadol- or tapentadol-treated groups (10, 25 or 50 mg/kg – typical effective analgesic dose, intermediate and maximum recommended doses, respectively). 24 h after intraperitoneal administration, biochemical and oxidative stress analyses were performed in blood, and specimens from brain, lung and heart were taken for histopathological and oxidative stress studies. Both drugs caused an increase in the AST/ALT ratio, in LDH, CK and CK-MB activities in serum samples, and an increase in lactate levels in serum and brain samples. Oxidative damage, namely protein oxidation, was found in heart and lung tissues. In histological analyses, tramadol and tapentadol were found to cause alterations in cell morphology, inflammatory cell infiltrates and cell death in all tissues under study, although tapentadol caused more damage than tramadol. Our results confirmed the risks of tramadol exposure, and demonstrated the higher risk of tapentadol, especially at high doses.